PEWARNA ALAMI EKSTRAK MASERASI BUNGA ROSELLA (Hibiscus sabdariffa L.) - Heru Nurcahyo; Kusnadi Kusnadi (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Rosella contains anthocyanin compounds that can be used as natural red dyes. This flower is also known to have many benefits (functional benefits) for health. Aside from being a dye, rosella (Hibiscus sabdariffa L.) can be used as a preservative, because it contains antioxidants and antibacterial. This research is a laboratory experiment study, which was carried out by maceration extraction method by giving an intervention at the temperature and pH of the carrier, using maceration extraction method, and the resulting extract was then isolated by anthocyanin and organoletically tested, pH and color absorption carried out by testing with UV-Vis spectrophotometry. The results of this study obtained absorbance values with the maximum absorption wavelength for the roselle natural red color sample was 510 nm. The best value of type B with intervention at acid pH with 1% citric acid content with emphasis at room temperature or 250C with an absorbance value of 1.544Keywords: Rosela, Anthocyanin, Maserasi